DETERMINANTS OF COMPANY SIZE, LEVERAGE, PROFITABILITY, ON CARBON EMISSION DISCLOSURE - Sindy, Winni; Leniwati, Driana; Prasetyo Nugroho Wicaksono, Agung; Haryanti, Agustin Dwi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
This research aims to test the influence of company size, leverage, profitability on carbon emission disclosure. This research uses mining companies listed on the Indonesia Stock Exchange during 2020. This research method uses a quantitative - associative design with secondary data sources, namely financial reports. There are 31 observation data. The analysis technique used is multiple linear regression with independent variables, namely company size, leverage, profitability and carbon emission disclosure as the dependent variable. The research results show that leverage has an effect on carbon emission disclosure. As for company size, profitability has no effect on carbon emission disclosure.